Assessment of crushed rock aggregates addition to granular lateritic materials in sub-Saharan extensive urbanization context (Yaoundé Cameroon) for road construction purposes - Ndzié Mvindi, Aloys Thierry; Lobe Bille, Jean Francis; Ngo’o Ze, Arnaud; Enock Embom, Christophe; Tsoyi À Koung, Emmanuel; Ngono Mbenti Emvana, Michèle Stella; Onana, Vincent Laurent (Discover Civil Engineering, 2024)
Granular lateritic materials (GLM) suitability for road construction after the addition of crushed rock aggregates (CRA) in the sub-Saharan extensive urbanization context was evaluated. The urbanization rate was made by using Landsat7 and Landsat8 radar images. The studied materials were subject to petrographic description and geotechnical analysis. The urbanized surface in the Yaoundé area increased by 41.88% from 2004 to 2020. The studied rock are gneisses composed of quartz, garnet, biotite, pyroxene, and feldspars. The gneisses obtained CRA have fines content of less than 10%, maximum dry density value of more than 2.00 g/cm 3 , good bearing capacity (CBR = 88%), and excellent mechanical characteristics (Los Angeles < 40%). This recommend their use as base course for low to medium volume traffic pavements. Gneisses-derived GLM, less load-bearing (CBR = 39 to 42%) than CRA, have limited behaviour in road construction and can be used as sub-base for all volume traffics. Their use in base courses requires prior treatment. CRA addition to these GLM result in the plasticity index decrease and compaction parameters improvement. CBR values increase shows a perfect correlation (R 2 > 0.90) with the addition of CRA. Litho-stabilised materials (CBR ≥ 60%) can be used as base course for low-volume trafficked pavements. The addition of a CRA percentage greater than or equal to 25% is efficient for the optimization of their use. By reducing the amount of quarry aggregates, the improved material could be an economical alternative for road projects. This reduces and controls the haulage of materials within crowded urban area.